1997
DOI: 10.1021/jp963252o
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of HDO into Single-Crystal H216O Ice Multilayers:  Comparison with H218O

Abstract: The diffusion of HDO into ultrathin single-crystal H2 16O ice multilayers was investigated using a novel combination of laser-induced thermal desorption (LITD) probing and isothermal desorption depth-profiling. The single-crystal hexagonal ice multilayers were grown epitaxially on a Ru(001) metal substrate, and the diffusion coefficients were measured perpendicular to the basal (0001) facet. The measured HDO diffusion coefficients ranged from D = (2.2 ± 0.3) × 10-16 to D = (3.9 ± 0.4) × 10-14 cm2/s over the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 39 publications
(91 reference statements)
8
57
0
Order By: Relevance
“…The activation energy of diffusion of HNCO within a NH 3 ice should be on the order of magnitude of a few 10 kJ mol −1 , the energy required to break few intermolecular hydrogen bonds (Park et al 2010). As a comparison the activation energy of the self-diffusion in bulk ice is E bulk a = 71±4 kJ mol −1 Livingston et al 1997). Therefore the diffusion of the molecules can be neglected between 8 and 60 K, on the time scale of our experiments, around 12 h typically.…”
Section: Kinetic Studies Of the Hnco + Nh 3 Reaction Using A Rate Equmentioning
confidence: 99%
“…The activation energy of diffusion of HNCO within a NH 3 ice should be on the order of magnitude of a few 10 kJ mol −1 , the energy required to break few intermolecular hydrogen bonds (Park et al 2010). As a comparison the activation energy of the self-diffusion in bulk ice is E bulk a = 71±4 kJ mol −1 Livingston et al 1997). Therefore the diffusion of the molecules can be neglected between 8 and 60 K, on the time scale of our experiments, around 12 h typically.…”
Section: Kinetic Studies Of the Hnco + Nh 3 Reaction Using A Rate Equmentioning
confidence: 99%
“…According to the literature [27][28][29][30][31][32], solid diffusion has a large activation energy. In fact, several experimental investigations showed that the activation energy for diffusion of the H 2 O molecule in the bulk ice was in the range of 52-70 kJ/mol [27][28][29][30][31]. On the other hand, Wang et al measured the kinetics of the CH 4 hydrate formation from neutron diffraction and reported that the activation energy for the diffusion in the hydrate phase was 61.5 kJ/mol [32].…”
Section: Replacement Mechanismmentioning
confidence: 99%
“…At higher temperatures, diffusional mixing is easier to perform due to molecular motion and self-diffusion. The activation energy of diffusion measured at the surface was E a surface = 14 ± 2 kJ mol −1 , whereas in the bulk it was E a bulk = 71 ± 4 kJ mol −1 (110,111). Thus, diffusion at the surface is more significant than in bulk at 100-140 K. This finding indicates higher mobility on the surfaces and demonstrates that reaction preferentially occurs on ice surfaces, rather than in the bulk, at low temperatures.…”
Section: Molecular Diffusion/intermixingmentioning
confidence: 86%
“…One of the most-studied types of molecular solids consists of self-assembled monolayers (SAMs), which are highly ordered molecular films grown on a well-defined surface, usually Au (111). To provide a glimpse into the diverse phenomena that can be observed through LEIS, we present the surprising finding of multiple fluorine abstraction by a single W + ion collision event on a…”
Section: Studies Using Self-assembled Monolayersmentioning
confidence: 99%